Scanning electron microscopy analysis of hair treated with pyloric cecae extract from pacu (Piaractus mesopotamicus) - Lopez, Juan Marcelo (2019)
Hair is composed mainly of keratin (90%) is a fibrous and insoluble protein with high content of amino acid cysteine, responsible of disulfide bonds presence, which gives it high resistance to degradation. Hair structure consists of a medulla, cortex, and cuticle. This last cover the cortex, made of long filaments packed together (microfibrils). Currently, the industrial processing of animal sources generates significant volumes of highly polluting waste. The meat packaging and tannery industry, hairdressing salon, generate waste of keratinous nature. On the other hand, aquaculture discards considerable amounts of viscera, but these are considered an alternative source of enzymes with potentials industrial applications. Treatment of these protein-rich wastes is an attractive option that results in products with high added value. In the present study we evaluated the degradative capacity on hairs of a pyloric cecae extract from pacu (Piaractus mesopotamicus) under reducing and non-reducing conditions. The extract was prepared by mechanical digestion of pacu viscera in buffer pH 7.8, 1:5 g tissue/ml and proteolytic activity were assayed over Nα-Benzoyl-dl-arginine-p-nitroanilide as substrate. Hairs were pre-treated with buffer 7.8, 1% 2-mercaptoethanol (2-ME), for 20 min at 100°C, then 5.0 U/ml pacu extract was added (1:5) and incubated for 1h, 3h, 24h and 7 days at 37°C. Hairs were observed at scanning electron microscopy (SEM). Other samples of the same hair were exposed in parallel under different treatments, such as the absence of reducing agent, heat or fish extract. SEM analysis showed that viscera extract, only in presence of 2-ME and heat, was able of degrading the hair cuticle, exposing the cortex microfibrils just at the first day. Results demonstrate that pyloric cecae pacu extract is able to degrade hair pre-treated with heat and reducing agent, so this treatment could be used in the recovery of hair keratins.